Redundancy allocation problem for k-out-of-n systems with a choice of redundancy strategies - Mahsa Aghaei; Ali Zeinal Hamadani; Mostafa Abouei Ardakan (Journal of Industrial Engineering International, 2017)
To increase the reliability of a specific system, using redundant components is a common method which is called redundancy allocation problem (RAP). Some of the RAP studies have focused on k-out-of-n systems. However, all of these studies assumed predetermined active or standby strategies for each subsystem. In this paper, for the first time, we propose a k-out-of-n system with a choice of redundancy strategies. Therefore, a k-out-of-n series-parallel system is considered when the redundancy strategy can be chosen for each subsystem. In other words, in the proposed model, the redundancy strategy is considered as an additional decision variable and an exact method based on integer programming is used to obtain the optimal solution of the problem. As the optimization of RAP belongs to the NP-hard class of problems, a modified version of genetic algorithm (GA) is also developed. The exact method and the proposed GA are implemented on a well-known test problem and the results demonstrate the efficiency of the new approach compared with the previous studies.
Keywords: 650; Redundancy allocation problem; Reliability optimization; Choice of redundancy strategies; k-out-ofn system